Evaluation of lumbar motion with fabric strain sensors: A pilot study - Vu, Linh Q.; Amick, Ryan Z.; Kim, K. Han; Rajulu, Sudhakar L. (International journal of industrial ergonomics, 2019)
Prolonged microgravity has been shown to have a deconditioning effect on the spine, increasing the risk of back issues at distant locations such as Mars. Therefore, studying the lumbar motion of astronauts inside a spacesuit during on ground assessments could be crucial for ensuring crew safety and performance on planetary extravehicular activities. However, spacesuits present many challenges in performing kinematic evaluations with conventional motion capture systems. The purpose of this investigation is to develop a methodology for evaluating lumbar motion that can be worn inside a spacesuit. This method, based on flexible strain sensors, was tested with unsuited subjects in this pilot study. Twelve male volunteer subjects performed unloaded lumbar sagittal flexion and lateral bending motions. Lumbar kinematics were concurrently measured from 3D body scans and flexible strain sensors attached to the subjects. Mean R2 values for flexion and lateral bending were 0.93 (±0.06) and 0.96 (±0.03) respectively, and mean estimated 95% error of ±5.3° and ±2.8° were determined for flexion and lateral bending, respectively. The results indicate that flexible strain sensors yield useful metrics for lumbar kinematics. Measuring biomechanics of the astronaut inside of a spacesuit is critical to improving spacesuit design and development of prophylactic countermeasures. However, the spacesuit prevents most traditional evaluation techniques. The method developed here provides a wearable solution to measure lumbar motion within the spacesuit and during field assessments in other industries. •Flexible strain-sensors provides a potential solution for measuring lumbar motion.•The sensor-predicted lumbar angles showed good agreement to the measured body angles.•Sensor signals may have varied between subjects due to anthropometry.•Future work is needed to address subject variation and refine sensor placement.